Optimization of the ellagic acid synthesis process at the bioreactor level using non-conventional yeasts (Brazilian Journal of Pharmaceutical Sciences, 2023)
Ellagic acid (EA) is a phenolic biomolecule. For its biosynthesis, a source of ellagitannins is required, such as strawberries and yeasts, as precursors of the tannase and β-glucosidase enzymes responsible for hydrolysis of ellagitannins. Two experimental mixture designs were applied., varying the yeast concentration and the number of ellagitannins in the culture medium, evaluating the enzymatic activity and ellagic acid biosynthesis. Aiming to find the optimal compositions of the non-conventional yeasts assessed in the research to biosynthesize ellagic acid feasibly and efficiently using a response surface performing the statistical analysis in the StatGraphics® program for obtaining a higher yield and optimizing the ellagic acid synthesis process, the results indicate that the strains Candida parapsilosis ITM LB33 and Debaryomyces hansenii ISA 1510 have a positive effect on the synthesis of ellagic acid, since as its concentration increases in the mixture the concentration of ellagic acid in the medium also increases; on the other hand, the addition of Candida utilis ITM LB02 causes a negative effect, resulting in the compositions of 0.516876, 0.483124 and 2.58687E-9 respectively, for a treatment under the same conditions, an optimal value of ellagic acid production would be obtained. With an approximate value of 7.33036 mg/mL.